2009
DOI: 10.2174/138945009788982441
|View full text |Cite
|
Sign up to set email alerts
|

New Drugs for Epidural Analgesia

Abstract: In recent years there has been a wide use of the epidural technique not only during surgery to provide anesthesia and analgesia, but also for obstetric and trauma as well as acute, chronic and cancer pain states. Nowadays there is an increase in the number of the epidural drugs. Local anesthetics and opioids are still the pharmacological agents more widely used epidurally, nevertheless other drugs from different pharmacological classes are administered as adjuvant to local anesthetics and opioids or are in var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 99 publications
0
25
0
2
Order By: Relevance
“…The obvious cases and outcomes of toxicity studies have often been attributed to ketamine's preservative, chlorobutanol [36]. A strong case can be made for the intrinsic toxicity of ketamine, however [32].…”
Section: Toxicitymentioning
confidence: 99%
“…The obvious cases and outcomes of toxicity studies have often been attributed to ketamine's preservative, chlorobutanol [36]. A strong case can be made for the intrinsic toxicity of ketamine, however [32].…”
Section: Toxicitymentioning
confidence: 99%
“…Clinical studies have shown opoid sparing effects of dexmedetomidine when used intravenously along with decrease in inhalational anesthetic requirement (4). It has also been reported to improve quality of intrathecal and epidural anesthesia (5, 6). However, very few clinical trials have studied the effect of dexmedetomidine in supraclavicular brachial plexus block.…”
Section: Introductionmentioning
confidence: 99%
“…In caudal block, the most used local anesthetic agent is bupivacaine, because it is readily available, has a long duration of action and its side effects are very well known 1215. A single-shot caudal injection of bupivacaine as sole local anesthetic provides effective postoperative analgesia 1213.…”
Section: Discussionmentioning
confidence: 99%